Political Science - Карпчук, Наталія Петрівна; Тихомирова, Євгенія Борисівна; Karpchuk, Nataliia P.; Tykhomyrova, Yevheniia B. (Lesya Ukrainka Eastern European National University, 2018)
Summary of the course : Politics as a social phenomenon. The subject, structure and paradigm of political science. Approaches to the definition of political science. Methodological Principles of Political Science. Background of Political Science. The concept of power as a social phenomenon. The origin and nature of the state. Forms of government and forms of territorial organization. Legal, social state: definition, nature, the basic features. The concept of the political process. The concept of political regime: its essence and core components. The essence of the political parties and their role in the political system of society. The subjects of the political process. Leadership and its specificity in the political aspects. Political consciousness as a reflection of political life. Political Ideology.
Keywords: політична влада; політична система; політичний процес; політична поведінка; політичні режими; political power; political system; political process; political behaviour; political regimes